Naaman: seine Heilung und Bekehrung im Alten und im Neuen Testament - Schöpflin, Karin (Biblische Notizen, 2009)
The story of the curing of Naaman’s leprosy is exceptional among the healings effected by prophets as it is prompted by an order given by the prophet sc. in the name of God. This means that the non-Israelite Naaman has to trust in the word’s effectiveness and act according to it. Therefore, this story combines curing and conversion. Within the NT Elisha and Naaman are explicitly mentioned only by Luke (4:27); however, the synoptic gospels characterize Jesus’ divine authority and power by alluding to 2Kgs 5. Also by implication the episode of the Ethiopian eunuch being baptized by Philippus includes references to the OT story, offering at the same time similar and contrasting traits.